KONFLIK DAN REKONSILIASI KONFLIK ANTARA SERIKAT BURUH DENGAN PT. DUTA PALMA NUSANTARA DI KABUPATEN KUANTAN SINGINGI - ", Zulhabibi; Asriwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted at PT. Duta Palma Nusantara Perkebunan Sei Kuko of Kuantan Singingi Regency with the aim to obtain information about conflict and reconciliation of conflict between union with PT. Duta Palma Nusantara. Some of the problems in this research are (1) How is reconciliation process between union with PT. Duta Palma Nusantara? (2) How is the source and trigger of conflict between union with PT. Duta Palma Nusantara. The title of this research is "Conflict and Reconciliation between Trade Unions with PT. Duta Palma Nusantara in Kuantan Singingi Regency ". This research was conducted to know the conflict reconciliation process and the source and trigger of conflict that happened between union with PT. Duta Palma Nusantara in Kuantan Singingi district. To find out how the conflict reconciliation process works. To know the source and trigger of conflict in PT. Duta Palma Nusantara. This research is a qualitative research because of its nature in the form of cases, which became the subject of this study selected based on those who know and are involved directly in the conflicts of industrial relations between the union with PT. Duta Palma Nusantara as many as 8 subjects. Used methods such as data collection, data collection techniques using observation, interview. To analyze the problems in this study used qualitative analysis and will be explained descriptively in writing. After this research, the results of this study describe the working relationship between laborers and PT. Duta Palma Nusantara is less harmonious and there is still a lot of gaps between the two, the lack of company attention to the workers makes the workers rise up and protest the policies made by the company. In this paper it is more closely related to how the reconciliation process between the two sides and the stages towards reconciliation of conflict that have been passed by both parties is by: Bipartite, Arbitration, Mediation, PHI, and Supreme Court stage. Where the stages have been successfully passed by both parties. In this paper will also discuss how sources and triggers the conflict that occurred between the union with PT. Duta Palma Nusantara.Keywords: Conflict Reconciliation, Source,Triggers